Christian Faith View On Mid-Brain Activation System And Its Impact On The Spirituality Of Children Aged 6 To 12 Years Old In Surabaya - Connie Laurina (Theological Journal Kerugma, 2021)
God created humans as the most special creation compared to His other creations. Human intelligence is caused by one organ which, although small in size, has a very vital role, namely the brain. Advances in knowledge and technology have encouraged scientists to try solving the mysteries of the brain. Many studies have focused on the right brain and left brain, or to balance the right brain and left brain. But in recent years, there has been a training/self-development institute who stated that they had found a way to balance the right and left brain, namely by activating the midbrain. This midbrain activation method is aimed at children aged 5-15 years because it is considered that children at this age are more easily activated in a very short time through a computer.The method used in writing this work is a Literature Study that contains various information on matters related to the topic of discussion. In addition to using literature, writing will be complemented by field research, using a Check List to interview respondents. The research approach used are qualitative and quantitative approach. A The qualitative approach obtains data regarding respondent's experiences. This writing has the aim of finding ( knowing ) whether the Midbrain Activation system is in accordance with God's Word or against God's Word; to open the horizons of parents, congregations and even readers of this paper, especially those with children, so that they can be more careful in choosing training for their children.